Involvement of the LlaKR2I methylase in expression of the AbiR bacteriophage defense system in Lactococcus lactis subsp. lactis biovar diacetylactis KR2 - Yang, Julie M. (2006)
The native lactococcal plasmid, pKR223, from Lactococcus lactis subsp. lactis biovar diacetylactis KR2 encodes two distinct bacteriophage-resistant mechanisms, the LlaKR2I restriction and modification (R/M) system and the abortive infection (Abi) mechanism, AbiR, that impedes bacteriophage DNA replication. This study completed the characterization of AbiR, revealing that it is the first Abi system to be encoded by three genes, abiRa, abiRb, and abiRc, arranged in an operon and that it requires the methylase gene from the LlaKR2I R/M system. An analysis of deletion and insertion clones demonstrated that the AbiR operon was toxic in L. lactis without the presence of the LlaKR2I methylase, which is required to protect L. lactis from AbiR toxicity. The novelty of the AbiR system resides in its original gene organization and the unusual protective role of the LlaKR2I methylase. Interestingly, the AbiR genetic determinants are flanked by two IS982 elements generating a likely transposable AbiR composite. This observation not only substantiated the novel function of the LlaKR2I methylase in the AbiR system but also illustrated the evolution of the LlaKR2I methylase toward a new and separate cellular function. This unique structure of both the LlaKR2I R/M system and the AbiR system may have contributed to the evolution of the LlaKR2I methylase toward a novel role comparable to that of the cell cycle-regulated methylases that include Dam and CcrM methylases. This new role for the LlaKR2I methylase offers a unique snapshot into the evolution of the cell cycle-regulated methylases from an existing R/M system.